2008
DOI: 10.21273/hortsci.43.7.2120
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Treatment for Chilling Injury Reduction of Astringent ‘Rojo Brillante’ Persimmon at Different Maturity Stages

Abstract: The effects of hot water treatments (HWTs) on chilling injury (CI) of ‘Rojo Brillante’ persimmon treated at different maturity stages and stored at 1 °C have been investigated. HWT temperatures ranging from 45 to 55 °C were applied for periods of time of between 2.5 and 40 min. Reduction of CI by HWT depended on the maturity stage. HWTs reduced softening when they were applied to fruit at an early stage of maturity, but caused skin cracking and skin browning in middle and advanced stages of maturity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Hence storage at low temperature is considered one of the most efficient tools to suppress fruit ripening as well as the development of decay. However, persimmon fruit shows chilling injury (CI) symptoms when stored at low temperature, 6 characterized by external browning with softening in which the susceptibility of this fruit to CI varies mainly with storage temperature and cultivar 7 . Also, the use of hypobaric and controlled‐atmosphere storage systems is expensive as well as difficult to run 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence storage at low temperature is considered one of the most efficient tools to suppress fruit ripening as well as the development of decay. However, persimmon fruit shows chilling injury (CI) symptoms when stored at low temperature, 6 characterized by external browning with softening in which the susceptibility of this fruit to CI varies mainly with storage temperature and cultivar 7 . Also, the use of hypobaric and controlled‐atmosphere storage systems is expensive as well as difficult to run 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Higher TSS in control fruit may be due to increased water loss and hydrolysis of starch into simple sugars. Previous studies have shown that hot water treatment is effective in lowering the starch hydrolysis in persimmon (Besada et al, 2008; Khademi et al, 2014) and Thai lime (Kaewsuksaeng et al, 2015). Naser et al (2018) also found that a combination of hot water and calcium lactate preserves the nutritional quality of persimmon fruits during postharvest storage.…”
Section: Resultsmentioning
confidence: 99%
“…According to Lima et al [53], during the growth and ripening of 'Fuyu' persimmon, fruit firmness decreases considerably, particularly during the last few days of the developmental period. This effect was more pronounced in astringent persimmons treated for 20 or 30 min at 45 ºC, which exhibited substantial softening [54]. The decline in firmness is due to the release of water and enzymatic activity that disrupts the cell wall [55] and this parameter may vary according to the fruit size [56].…”
Section: Discussionmentioning
confidence: 99%